Ecological psychology as social psychology?. (December 2020) - Heft, Harry
Several articles published in this journal over a number of years have examined the social dimensions of Gibsonian ecological psychology. The present paper picks up several of their themes, with an emphasis on the social developmental consequences of individuals participating in community structures and engaging the affordances that support them. From this perspective, the situated nature of activity in everyday settings is examined, which in turn highlights the role of places as higher order emergent eco-psychological structures (or behavior settings) in everyday life. Moreover, ecological psychology's discovery of occluding edge effects, which demonstrates that objects that have gone out of sight are experienced as persisting in awareness, serves as the basis for a proposal that the awareness of social structures of a conceptual nature may arise from the pragmatics of perception–action from an ecological perspective.